Challenges of brain-computer interface facilitated cognitive assessment for children with cerebral palsy - Huggins, Jane E.; Karlsson, Petra; Warschausky, Seth A. (Frontiers in Human Neuroscience, 2022)
Brain-computer interfaces (BCIs) have been successfully used by adults, but little information is available on BCI use by children, especially children with severe multiple impairments who may need technology to facilitate communication. Here we discuss the challenges of using BCI with children, especially children who do not have another established method of communication with unfamiliar partners. Strategies to manage these challenges require consideration of multiple factors related to accessibility, cognition, and participation. Appropriate consideration of these factors revolves around the answer to three questions: 1) Where (home, clinic or lab) will participation take place? 2) How many sessions will be involved? 3) What degree of participation is expected from the child? Careful consideration of how to answer these questions while addressing the challenges inherent in BCI use by children with disabilities will establish a basis on which successful BCI calibration and adoption of BCI as an access method can occur.